Return to happiness - Michot, Khalil; Phillips, Ryan John; Little Studio Films; Leomark Studios (Firm) ([Beverly Hills, Calif.] : Little Studio Films, 2013)
The film is about the dramatic events that changed the life of former Canadian professional hockey player Ryan Phillips. Ryan began this movement after facing a series of serious challenges that derailed his professional sports career and led to his incarceration for the illegal distribution of marijuana in a USA prison. Upon his release, Phillips was prohibited from re-entering the United States and was separated from the love of his life, his daughter Sadie. Trying to cope with his new life, Phillips embarked on a series of adventures throughout South East Asia resulting in the manifestation of a spiritual growth and social activism including his involvement with the Somaly Mam project. --
Originally released as a motion picture in 2013
Ryan John Phillips, Serind Swan, Somaly Mam, Grand Phillips, Cindy Phillips, Sadie Phillips, Julien Jorgensen.
Cinematographer, Khalil Michot ; editor, Tyler Hotman.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 2, 2018)
Keywords: Phillips, Ryan John; Marijuana abuse; Hockey players -- Canada -- Biography; Happiness; Self-realization.; Biographical films; Documentary films; Internet videos; Streaming video